Calculation of the calibration parameterNRSK of different types of comets - Hanash, Ruaa Faraj; Khalaf, Salman Zaidan (Iraqi Journal of Science, 2024)
This paper gives a dynamic analysis of the recently identified calibration parameter (NRSK) in the distance modulus equation for all celestial planets. The parameter NRSK has been applied for seven different comets from the Kuiper-Belt region: (1P/Hally, C/2023 E1 (ATLAS), 23P/Brorsen-Metcalf, 20D/Westphal, 12P/Pons-Brooks, 13P/Olbers, and C/2022 P1 (NEOWISE)). This was accomplished by programming data from the Live Sky program from previous years. It is determined that each comet has a distinctive NRSK that distinguishes it from other comets and that this parameter does not equal one. According to the data, the seven comets' average NRSK is (2.53 for 1P/Hally, 2.561forC/2023 E1 (ATLAS), 2.57 for 23P/Brorsen-Metcalf, 3.07 for 20D/Westphal, 4.11 for 12P/Pons-Brooks, 4.12 for 13P/Olbers, and 3.07 for C/2022 P1 (NEOWISE).